A reflectarray design with reduced crosspolarization for polarimetric radar. Issue 8 (August 2014) - Pan, Yu; Zhang, Yan (Rockee); Yu, Xining
ABSTRACT Polarimetric weather radar provides more accurate information about precipitation rates. As the precipitation detection in dual‐polarimetric measurements relies on complete isolation of orthogonal components of the fields, a low crosspolarization radiation is desirable. In this article, a reflectarray with gapped double‐ring elements was designed to suppress the crosspolarization level at and around broadside. In this design, gaps are cut on the double‐ring elements to change the directions of the surface currents, so the crosspolar components will cancel each other along the broadside direction, and thus a low crosspolarization level can be achieved. Both simulation and measurements were carried with the new design, and a crosspolarization level of −44 dB at broadside and less than −33 dB for all azimuth ranges (−90° < θ < 90°) was achieved in measurements. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1879–1883, 2014